Surface-mounted acoustic vector-sensor array processing - Hawkes, M.; Nehorai, A. (1996 IEEE International Conference on Acoustics, Speech, and Signal Processing Conference Proceedings, 1996)
We consider the passive direction-of-arrival (DOA) estimation problem using arrays of acoustic vector-sensors located in a fluid, at or near a plane boundary. We formulate a general measurement model applicable to most surfaces, and derive an expression for the Cramer-Rao bound (CRB) of a single source. The CRB is used to analyze the practically important cases of ideal rigid and pressure-release surfaces in detail. An important quantitative comparison is made between a stand-off array of pressure sensors and a surface-mounted array of velocity sensors for the latter surface. In particular, we define and find an expression for the critical distance, at which the arrays have an equivalent performance.